Appendicular Mass: A Conservative Approach - Koirala, Ashok; Thakur, Dipendra; Agrawal, Sunit; Pathak, Kamal Raj; Bhattarai, Manoj; Sharma, Abhilasha (Journal of Nobel Medical College, 2016)
Introduction Appendicular mass is one of the most common complications following acute appendicitis and seen in 2-6% of the patients. The treatment of appendicular mass is controversial with three general approaches. The aim of this study is to evaluate outcome of conservative approach. Material & Methods A retrospective analysis of the patients managed with appendicular mass from 1st January to 31st December 2014 was carried out in NMCTH, Biratnagar. A total of 173 patients with diagnosis of appendicular mass admitted in emergency and OPD of our hospital were studied. All age groups and both sex were included. Results Out of 496 patients with appendicitis, 173 patients [34.87%] were diagnosed with appendicular mass. Age range of the patient in the study varied between 4-84 years and maximum patients found in the age group of 21-30 years. Onset of symptoms was between 2-6 days and greater number of patients reporting between 5-6 days. During study period 10(5.7%) patients came with recurrence, 9 [5.2%] developed abscess, 35(20.23%) patients came for interval appendicectomy, whereas 119 [68.78%] failed to come for a follow up. Conclusion Our study concluded that the appendicular mass can be managed successfully by conservative approach, although few complications may arise which can be managed by surgical intervention. Journal of Nobel Medical College Vol.5(2) 2016; 47-50